Pareto’s Non-logical Actions and the Issue of Humanity - D’Andrea, Fabio (Italian Sociological Review, 2024)
In this essay I put forward the hypothesis that Pareto’s theory of action should be understood as an unintentional, pioneering study on the complexity of humanity rather than as an attempt to explain and correct non-logical behaviours. Through a critical reading of Pareto’s vocabulary and unspoken convictions, it will be shown that he went well beyond his own intentions highlighting a fundamental – though unacknowledged and stigmatized – dynamics of human interaction and organization. Building on Pareto’s evidence of the importance of non-logical action, it is possible to free humanity from the normative obligation to be rational and begin to understand the actual complexity of interaction and culture creation, taking into account heuristic spheres that rationalization has banned from awareness, but are still crucial, unbeknownst to us: corporeity, emotions, symbolic-imaginal thinking.